A novel bladder phenotype in junctional epidermolysis bullosa: a case report - He, Qingbao; Gui, Meng; Wang, Hao; Zhang, Lei (Frontiers in Pediatrics, 2025)
BackgroundJunctional epidermolysis bullosa (JEB) is a rare inherited blistering disorder, and its urological spectrum remains poorly defined.Case PresentationA 19-month-old boy carrying compound heterozygous ITGB4 mutations (p.R252C, p.P305l) had a 17-month history of intermittent voiding. Ultrasound demonstrated focal papillomatous bladder-wall thickening, and cystoscopy showed scattered follicular mucosal changes without masses. Biopsies revealed mild oedema and chronic lymphocytic inflammation; no malignancy. Urine cultures were negative.ConclusionThis case broadens the reported urological spectrum of ITGB4-related JEB by illustrating a papillomatous–follicular bladder phenotype. Early urological evaluation in patients with JEB presenting with unexplained urinary symptoms may facilitate timely, targeted management and help prevent chronic complications.